2019
DOI: 10.3389/fnins.2019.00056
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin Facilitates Social Learning by Promoting Conformity to Trusted Individuals

Abstract: There is considerable interest in the role of the neuropeptide oxytocin in promoting social cohesion both in terms of promoting specific social bonds and also more generally for increasing our willingness to trust others and/or to conform to their opinions. These latter findings may also be important in the context of a modulatory role for oxytocin in improving the efficacy of behavioral therapy in psychiatric disorders. However, the original landmark studies claiming an important role for oxytocin in enhancin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 103 publications
1
30
0
2
Order By: Relevance
“…Oxytocin is synthesised within the hypothalamus and is stored in and released by the pituitary (Meyer-Lindenberg, Domes, Kirsch, & Heinrichs, 2011) in response to stimuli like touch, eye gaze, massage, intimacy and playful interactions (Uvnas-Moberg & Petersson, 2005). Oxytocin is well-established as an enhancer of social behaviour and feelings of togetherness and has been proposed as a key neurotransmitter associated with social competence (Declerck, Boone, & Kiyonari, 2010), pair bonding (Liu & Wang, 2003) and social learning (Xu, Becker, & Kendrick, 2019). As dopamine and oxytocin can create interactions between reward and the social brain centres, including the nucleus accumbens (Liu & Wang, 2003), it might be part of the physiological mechanism behind the proverb 'the family that plays together stays together'.…”
Section: Physiology Of Playmentioning
confidence: 99%
“…Oxytocin is synthesised within the hypothalamus and is stored in and released by the pituitary (Meyer-Lindenberg, Domes, Kirsch, & Heinrichs, 2011) in response to stimuli like touch, eye gaze, massage, intimacy and playful interactions (Uvnas-Moberg & Petersson, 2005). Oxytocin is well-established as an enhancer of social behaviour and feelings of togetherness and has been proposed as a key neurotransmitter associated with social competence (Declerck, Boone, & Kiyonari, 2010), pair bonding (Liu & Wang, 2003) and social learning (Xu, Becker, & Kendrick, 2019). As dopamine and oxytocin can create interactions between reward and the social brain centres, including the nucleus accumbens (Liu & Wang, 2003), it might be part of the physiological mechanism behind the proverb 'the family that plays together stays together'.…”
Section: Physiology Of Playmentioning
confidence: 99%
“…In humans, pharmacological studies have demonstrated oxytocin’s role in social cognition in healthy subjects and in psychiatric patients ( Ishak et al, 2011 ; Meyer-Lindenberg et al, 2011 ). For example, intranasal oxytocin increases the perceived trustworthiness of faces ( Theodoridou et al, 2009 ), improves the accuracy of mental-state inferences ( De Dreu et al, 2011 ; Domes et al, 2007 ; Guastella et al, 2010 ), enhances learning from social cues ( Hurlemann et al, 2010 ) and seems to increase conformity ( De Dreu and Kret, 2016 ; Xu et al, 2019 ), particularly in a competitive context ( Aydogan et al, 2017 ). In game theory tasks, it increases generosity ( Barraza et al, 2011 ; Zak et al, 2007 ), cooperation ( Declerck et al, 2010 , 2013 ; Ditzen et al, 2009 ) and trust ( Bakermans-Kranenburg and Van IJzendoorn, 2013 ; Kosfeld et al, 2005 ), although not consistently replicated ( Nave et al, 2015 ), while vasopressin has increased mutual cooperation ( Brunnlieb et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, low statistical power [8,9] and replicability of findings [10] of intranasal OXT administration experiments have become a matter of growing concern. Indeed, recent comprehensive replication studies failed to replicate modulatory effects of intranasal OXT on core domains initially associated with OXT, including 'mind reading' [3,11] as well as trust -both when money ( [1]; for contrasting findings [12], critical review by [10]) or confidential personal information were at stake (see review [13]).…”
Section: Introductionmentioning
confidence: 99%